Families and Crime. (October 2018) - Parcel, Toby L.; Hoffmann, John P.
This volume highlights the theoretical and empirical connections between family sociology and criminology. We review the historical interconnections between these two fields. We argue for greater intellectual conversation across the two areas, and then we identify several elements they hold in common. These include their use of social theory, their attention to human development, and their use and appreciation of longitudinal research. We conclude with brief overviews of the six articles that make up this special issue.